Korean popular culture: an exploratory examination among Malaysian adolescents - Zainal Ariffin, Zailin; Abdul Rahman, Azmawani; Omar, Siti Sarah; Yaakop, Azizul Yadi; Mahadi, Nomahaza (Medwell Online, 2016)
In the early 2010s, there has been an increasing interest in the varieties of products and images of South Korean popular culture around the world, a development led by popular music. The Korean popular culture has influenced youth consumption patterns. Today, information has a great influence on the values and lifestyle of society and also gives consumers a lot more options. Teenagers especially are very fond of American popular music, film and fashion because those are what they often see through broadcasting and entertainment. This opportunity has been used by South Korea to commercialize their culture as a commodity package through Hallyu. There is a need to look to Korea popular culture in every dimension because popular culture has a unique set of dimension. This study identifies the critical dimensions of Korean popular culture among adolescents living in the Klang valley. A study was conducted by an exploratory examination among Malaysian adolescents.